In situ microbiota distinguished primary anthropogenic stressor in freshwater sediments. (August 2018) - Xie, Yuwei; Floehr, Tilman; Zhang, Xiaowei; Xiao, Hongxia; Yang, Jianghua; Xia, Pu; Burton, G. Allen; Hollert, Henner
Abstract: Conventional assessment and evaluation of sediment quality are based on laboratory-based ecotoxicological and chemical measurements with lack of concern for ecological relevance. Microbiotas in sediment are responsive to pollutants and can be used as alternative ecological indicators of sediment pollutants; however, the linkage between the microbial ecology and ecotoxicological endpoints in response to sediment contamination has been poorly evaluated. Here, in situ microbiotas from the Three Gorges Reservoir (TGR) area of the Yangtze River were characterized by DNA metabarcoding approaches, and then, changes of in situ microbiotas were compared with the ecotoxicological endpoint, aryl hydrocarbon receptor (AhR) mediated activity, and level of polycyclic aromatic hydrocarbons (PAHs) in sediments. PAHs and organic pollutant mixtures mediating AhR activity had different effects on the structures of microbiotas. Specifically, Shannon indices of protistan communities were negatively correlated with the levels of AhR mediated activity and PAHs. The sediment AhR activity was positively correlated with the relative abundance of prokaryotic Acetobacteraceae, but had a negative correlation with protistan Oxytrichidae . Furthermore, a quantitative classification model was built to predict the level of AhR activity based on the relative abundances of Acetobacteraceae and Oxytrichidae . These results suggested that in situ Protista communities could provide a useful tool for monitoring and assessing ecological stressors. The observed responses of microbial community provided supplementary evidence to support that the AhR-active pollutants, such as PAHs, were the primary stressors of the aquatic community in TGR area. Graphical abstract: Image 1 Highlights: The diversity of Protista communities was negatively correlated with AhR mediated activity and PAHs in sediments. The level of AhR activity can be predicted by the relative abundances of Acetobacteraceae and Oxytrichidae. In situ Protista communities provide a useful tool for monitoring and assessing sediment quality.